The role of information and communications technology in research capacity building - BRENNAN, NIAMH (The Irish-African Partnership for Research Capacity Building, 2010)
Reliable, accessible, high speed Internet and network connectivity is a fundamental requirement for the conduct of high quality, high-impact research today. High speed communications are part of the basic infrastructure of a modern university, supporting efficient administration, ensuring a global presence on the web and helping with managing student information systems. The focus of this chapter is on those elements of the Information and Communications Technology (ICT) infrastructure which are directly relevant to RCB; specifically National Research and Education Networks, Research Support Systems and Digital Repositories, and finally e-Learning technologies that support research-led teaching. A key theme running through this chapter is that of collaboration and the need for a cooperative approach both within and among institutions in order to deliver a robust and cost-effective ICT infrastructure.
Research capacity building for development: resources for higher education institutions
PUBLISHED
Belfast
Keywords: International development; Research capacity building; Open Access; Current Research Information Systems (CRIS); Inclusive Society; International Development